2023
DOI: 10.1111/opn.12577
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of social connectedness in older adults living in congregate long‐term care settings: A systematic review of quantitative and qualitative evidence

Emily Lim,
Natalia Nielsen,
Lucienne Lapane
et al.

Abstract: BackgroundThe overall impact of social connectedness on health outcomes in older adults living in nursing homes and assisted living settings is unknown. Given the unclear health impact of social connectedness for older adults in congregate long‐term care settings worldwide, a comprehensive systematic review is required to evaluate the overall relationship between social connectedness and health outcomes for them.ObjectivesThe purpose of this article was to synthesize the literature regarding the health impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 221 publications
0
4
0
Order By: Relevance
“…Specifically, participants in the Social Connectedness Workshop reported reduced engagement in risk-taking behaviors and enhanced abilities in mood regulation at post-intervention and at a three-month follow-up. These outcomes underscore the significant role of social connectedness as a protective factor in mental health and behavioral regulation, aligning with a growing body of research that emphasizes the importance of social bonds and support systems in mitigating psychological distress and promoting well-being (Fox, 2023;Lim, 2023).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Specifically, participants in the Social Connectedness Workshop reported reduced engagement in risk-taking behaviors and enhanced abilities in mood regulation at post-intervention and at a three-month follow-up. These outcomes underscore the significant role of social connectedness as a protective factor in mental health and behavioral regulation, aligning with a growing body of research that emphasizes the importance of social bonds and support systems in mitigating psychological distress and promoting well-being (Fox, 2023;Lim, 2023).…”
Section: Discussionmentioning
confidence: 62%
“…The significant improvements in mood regulation observed in the study participants also highlight the therapeutic potential of enhancing social connectedness. Previous research has demonstrated the health benefits of social ties, particularly in mitigating the effects of social isolation and loneliness on mental health (Lim, 2023;Ransome, 2023). By providing a structured framework for participants to connect with others and build meaningful relationships, the workshop directly addressed one of the critical determinants of emotional well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations